PENGUATAN USAHA KECIL MENENGAH MELALUI PROGRAM TANGGUNG JAWAB SOSIAL PERUSAHAAN (Studi pada PT INKA Persero) - Tatik Mulyati; Saraswati Budi Utami (CAPITAL: Jurnal Ekonomi dan Manajemen, 2019)
One of CSR PT INKA (Persero) programme is partnership that increase small business in order to be a resilient and independent business. PT INKA (Persero) is one of BUMN that bounded with obligation to implement Corporate Social Responsibility (CSR) programme as an actualization company’s activity. In its implementation, the CSR partnership programme has not effective yet by its planning, implementation or restraint. The human resources’s problem, nothing assistancing and monitoring its implementation, can be reduced if implemented by other support including a university. The aim of this research are: 1) Understanding the implementation of CSR partnership programme had done by PT INKA (Persero); 2) Understanding an obstacle in CSR partnership programme; 3) Understanding the effectivity of implementation CSR partnership programme. The respondent is a micro enterpreneur that guidanced by PT INKA (Persero). The population are 424 partners that spread out in Bakorwil Madiun and samples are 88 partners that taken by Cluster Convenience Sampling. Data was collected by interview, questionnaire and documentation. Using Wilcoxon Match Pairs test to know output’s effectivity with comparing before and after receiving funds’s programme of CSR. The results, there are significant differences between before and after receiving revolving funds as CSR’s programme. It shows that CSR partnership’s programme are effective for strengthening economic community especially partner of PT INKA (Persero).Keywords: small and medium enterprises, CSR, partnership’s programme, empowerment’s economic